Power, community mobilization, and condom use practices among female sex workers in Andhra Pradesh, India. - Blankenship, Kim M; West, Brooke S; Kershaw, Trace S; Biradavolu, Monica R (AIDS (London, England), 2008)
We used a structural interventions framework to analyse the associations between power and condom use among a sample of female sex workers (FSW), and how exposure to a local community mobilization intervention (CMI) affects these associations.
Keywords: Adult; Age Distribution; Community Networks; Condoms; Cross-Sectional Studies; Female; Health Promotion; HIV Infections; Humans; India; Internal-External Control; Middle Aged; Power (Psychology); Prostitution; Safe Sex; Socioeconomic Factors; Young Adult